Radiological risk and mineralogical analysis of radionuclides in granitic rocks: Environmental insights - Sherif A. Taalab; Diaa A. Saadawi; Turki Kh Faraj; Mayeen Uddin Khandaker; Mahmoud R. Khattab; Mohamed Y. Hanfi (Nuclear Engineering and Technology, 2025)
This study investigates the activity concentrations of naturally occurring radionuclides, particularly 238U, 232Th, and 40K, in granitic rocks from the Gabal Abu Garadi region in Central-Eastern Egypt. Using high-purity germanium gamma-ray spectrometry, these radionuclides were quantified and evaluated their spatial distribution and mineralogical associations. The mean concentrations of 232Th and 238U were found to be 3944 Bq kg−1 and 6554 Bq kg−1, respectively—significantly exceeding global average values reported by UNSCEAR. Radiological hazard indices, including absorbed dose rate (Dair), annual effective dose (AED), radium equivalent activity (Raeq), annual gonadal dose equivalent (AGDE), and excess lifetime cancer risk (ELCR) were subsequently calculated to assess the potential health risks posed by these elevated levels. Principal Component Analysis (PCA) and correlation analyses revealed 238U as the primary contributor to radiological risk in the region. The integration of petrographic and mineralogical studies confirmed the presence of uranium- and thorium-bearing minerals such as uranothorite, thorite, zircon, monazite, and samarskite. The findings highlight the necessity for regulatory oversight and radiation protection measures in areas with similarly enriched geological settings.